2012
DOI: 10.1021/nl302200w
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Mediated off-Resonance Plasmonic Enhanced Ultrafast Laser-Induced Nanocavitation

Abstract: The generation of nanobubbles around plasmonic nanostructures is an efficient approach for imaging and therapy, especially in the field of cancer research. We show a novel method using infrared femtosecond laser that generates ≈800 nm bubbles around off-resonance gold nanospheres using 200 mJ/cm(2) 45 fs pulses. We present experimental and theoretical work that demonstrate that the nanobubble formation results from the generation of a nanoscale plasma around the particle due to the enhanced near-field rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

15
206
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(225 citation statements)
references
References 55 publications
15
206
1
3
Order By: Relevance
“…However, the best rule is to avoid such distorted signals because they may lead to misinterpretation of the bubble parameters. 58 In all three considered cases (single NB, single NB with misaligned probe beam, and multiple NBs), the durations of the bubble-specific signals could be linked to the maximal diameter of the NB (or the largest NB as in Figure 2(b-I)), while their amplitudes differed significantly and, therefore, their use as NB metrics may lead to artifacts. 59 The third method of NB detection employs the pressure waves generated during the bubble expansion and collapse 23,26 ( Figure 1(c)).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…However, the best rule is to avoid such distorted signals because they may lead to misinterpretation of the bubble parameters. 58 In all three considered cases (single NB, single NB with misaligned probe beam, and multiple NBs), the durations of the bubble-specific signals could be linked to the maximal diameter of the NB (or the largest NB as in Figure 2(b-I)), while their amplitudes differed significantly and, therefore, their use as NB metrics may lead to artifacts. 59 The third method of NB detection employs the pressure waves generated during the bubble expansion and collapse 23,26 ( Figure 1(c)).…”
mentioning
confidence: 87%
“…If such absorbance emerges (due to plasma formation or any non-linear modification of the optical properties of the media), the method may characterize an NB incorrectly. 58,59 In another method, the beam is pointed off the detector aperture and produces a low base level at the detector. In this case, only the light scattered by an NB will reach the detector and will increase its output signal, also producing a time-response with a bubble-specific shape.…”
mentioning
confidence: 99%
“…The interactions, which lead to membrane permeabilization, are based on heating of the particle or nanocavitation due to the near-field enhancement. 6,7 The main disadvantage of all techniques is the incubation with the gold nanoparticles. First, it is time-consuming, which limits the high-throughput applicability in routine usage.…”
mentioning
confidence: 99%
“…We have shown that the LIB of trapped polystyrene nanoparticles significantly reduced the energy required for cavitation [6,7]. This leads to the permeabilization of cell membranes and transfection of cells in a targeted area in the absence of a lysis zone of cells.Gold nanoparticle clusters have played a key role in this field, through antibody binding and sequestration with subsequent irradiation by nanosecond or femtosecond laser pulses [8][9][10]. A unique interaction of gold nanoparticles with light, known as surface plasmon resonance, can lead to strong absorption of light for heat generation.…”
mentioning
confidence: 99%
“…Gold nanoparticle clusters have played a key role in this field, through antibody binding and sequestration with subsequent irradiation by nanosecond or femtosecond laser pulses [8][9][10]. A unique interaction of gold nanoparticles with light, known as surface plasmon resonance, can lead to strong absorption of light for heat generation.…”
mentioning
confidence: 99%